PENANGANAN POTENSI KONFLIK KEAGAMAAN DI CIGUGUR KABUPATEN KUNINGAN - Ahsahul Khalikin (Harmoni, 2014)
This qualitative study aims to describe the pattern of the resolution of conflict with religious characteristics by government and civil society actors in Cigugur. This study looks at the use of local wisdom by the FKUB in resolving conflict as well as the provisions of PBM No. 8 and 8 of 2006. In Cigugur village, “religious” conflict was often resolved through the bonds of kinship solidarity and by emphasizing the similarities amongst the Sundanese coethnics. The recommendations of this study are: the Pluralism and toerance of Cigugur should be preserved as a model of religious harmony based on local wisdom. The pattern of harmonious interaction between interreligious communities in Cigugur should be a model for religious conflict resolution in other areas while still taking consideration of local wisdom in those areas. The study also finds thw need for the socialization of the Joint Ministerial Decree No. 9 and 8 of 2006.